2020
DOI: 10.22452/iojel.vol3no1.4
|View full text |Cite
|
Sign up to set email alerts
|

Headmasters’ Safety Management and Performance in Two Malaysian National Primary Schools

Abstract: A conducive environment to ensure safety among school students is crucial as most of the time they are at school and grow up in school settings. It is vital to understand that, this period is a critical development stage for students whereby their personality is developed holistically in a different environment from home. The failure of handling hazards effectively and neglecting attitude on reporting cases contributes to the rising number of accidents in schools. Thus, the study aims to explore headmasters' s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The countries where the studies were conducted are shown in Figure 2. Out of 21 selected articles, seven studies were conducted in United State of America [7,20,41,[44][45][46]49], three studies were conducted in Malaysia [10,36,38], two studies were conducted in Turkey [23,39], two studies in Taiwan [21,42], one study was conducted in these countries, namely Canada [43], Sweden [37], Finland [40], Iran [22], Spain [24], Iraq [48], and Saudi Arabia [47]. The total number of articles published each year is displayed in Figure 3.…”
Section: General Findings and Background Of The Studies Included In T...mentioning
confidence: 99%
See 3 more Smart Citations
“…The countries where the studies were conducted are shown in Figure 2. Out of 21 selected articles, seven studies were conducted in United State of America [7,20,41,[44][45][46]49], three studies were conducted in Malaysia [10,36,38], two studies were conducted in Turkey [23,39], two studies in Taiwan [21,42], one study was conducted in these countries, namely Canada [43], Sweden [37], Finland [40], Iran [22], Spain [24], Iraq [48], and Saudi Arabia [47]. The total number of articles published each year is displayed in Figure 3.…”
Section: General Findings and Background Of The Studies Included In T...mentioning
confidence: 99%
“…The total number of articles published each year is displayed in Figure 3. Out of 21 selected articles, three articles were published in 2021 [47][48][49], three articles in 2017 [24,44,45], three articles in 2015 [10,23,37], two articles in 2019 [38,46], two articles in 2016 [39,40], two articles in 2014 [22,43], two articles in 2008 [21,42], one article in 2011 [41], one article in 2007 [20], one article in 2020 [36], and one article in 2005 [7]. Most of the selected articles were about leadership practices for safety in higher education institutions with 13 articles (62%), and another 8 articles (38%) were about leadership practices for safety in schools at the primary and secondary levels.…”
Section: General Findings and Background Of The Studies Included In T...mentioning
confidence: 99%
See 2 more Smart Citations
“…As for management studies, only 9% of studies typically examined quality and accountability processes (Abdul Khalil and Awang, 2016;Ismail and Don, 2015), discipline management (Ghani et al, 2014), curriculum management (Awang Besar and Hj Ahmad, 2013;Mohd Hamzah and Ayob, 2015), safety management (Naranasamy and Adams, 2019;Ramachandran and Kenayathulla, 2018), conflict management (Khun-inkeeree et al, 2019), financial management (Mohd Arus et al, 2018), and human resource management (Hj Ahmad, 2009). The distribution of the Malaysian EDLM studies corroborates with the global literature in EDLM, which has demonstrated a preference on studying leadership in recent years (Mertkan et al, 2016).…”
Section: Leadership and Managementmentioning
confidence: 99%